Intellectual capital performance and profitability of banks: Evidence from Pakistan - Muhammad Haris; Hongxing Yao; Gulzara Tariq; Ali Malik; Hafiz Mustansar Javaid (Journal of Risk and Financial Management, 2019)
The study contributes to the existing literature on intellectual capital (IC) performance and profitability by extending evidence from Pakistan. The study examines the impact of IC performance on the profitability of Pakistani financial institutions. It further examines how corporate governance, bank specific, industry specific, and country specific indicators effect Pakistani banks' profitability. The result reports both the linear and non-linear impact of IC performance on profitability, which affirms an inverted U-shaped relationship. Among the three value added intellectual coefficient (VAIC) components, capital employed efficiency (CEE), and human capital efficiency (HCE) are found to have a significantly positive and structural capital efficiency (SCE) is found to have a significantly negative impact on bank profitability. The study notes a positive impact on profitability of factors like board independence, directors' compensation, and higher capitalization. It reports a negative impact on profitability of factors like board size, board meetings, credit risk, industry concentration and economic growth. The results also indicate low profitability of banks during the period of government transition. The study provides insights into the important profitability drives and suggests that the impact of investment in IC on profitability is limited to an extent. The findings of this study are likely to be useful for policy makers, management, and academics.
Keywords: 330; Pakistan; banks; profitability; intellectual capital; generalized method of moments (GMM)